Physical rehabilitation after knee arthroscopy with meniscus injury - Gulbani R.Sh; Pakulya N.V (Kharkov National Pedagogical University, 2010)
Influence of facilities of physical rehabilitation is examined on the change of indexes of the functional and physical state of knee-joint after arthroscopic operation at the damage of meniscuses. There were 20 men in age from 22 years to 41 year. The results of inspection of the state of knee-joint are presented to the rehabilitation (right after arthroscopic interference) and upon termination of rehabilitation measures. Application of the facilities of physical rehabilitation offered by us for patients after arthroscopic meniscectomies gave positive results.